Dynamics of Freezing and Warming of Soft Tissues with Short-Term Eﬀect on Skin with Cryoapplicator - Kovalov , Gennady; Gordiyenko , Eduard; Fomenko , Yulia; Shustakova , Galyna; Kiporenko , Polina; Oleﬁrenko , Oleksiy (Problems of Cryobiology and Cryomedicine, 2020)
The paper presents the analysis of possibilities and limitations of using the thermal imaging to monitor the dynamics of temperature ﬁeld caused by a short-term cryoablation. It is shown that the method allows to remote and intraoperative control the dynamics of the freezing zone diameter as well as to estimate the current diameter of primary cryonecrosis zone. The diameter of primary cryonecrosis zone for this type of tissues reaches 13 mm, which makes it possible to destroy small morbid growth by low temperatures even with a short-term (30 s) cryoexposure. The using of this method to monitor the process of natural warming has shown the presence of long quasistable stage in dynamics of the freezing zone diameter with a slight change in the temperature ﬁeld. This fact is likely due to structural changes in frozen tissues. Probl Cryobiol Cryomed 2020; 30(4): 359–368